Paediatric emergency departments in Nigeria: how prepared are they to provide emergency care - Enyuma, Callistus Okwuchukwu Achuri (My University, 2019)
Introduction: Paediatric emergency care is poorly developed in low and middle-income countries. Established Paediatric Emergency Department (PED) facilities face significant challenges. The magnitude of challenges facing the PED in Nigeria has not been well described. This study aimed to assess paediatric emergency care preparedness across PEDs in Nigeria. Methods: This cross-sectional questionnaire-based study of PEDs in Nigeria recruited facilities across various regions of the country. A self-administered questionnaire and a check list were used to obtain information on the availability of skilled personnel, medications and equipment. Preparedness performance was assessed using a point score scale. Results were described, compared and correlated. Results: Of the 34 studied PEDs, 52.9% (n=18) were located in the North region of Nigeria. The mean (SD) number of patient visits and admission to short-stay wards within the last 30-days prior to data collection was 253.2 (±261.2) and 116.4 (±68.3) patients respectively. Most (70.6%) PEDs ran 2 shift duties per day. Most of the resident doctors (70.4 %) and nurses (85.3%) did not have Basic Life Support certification. The mean managerial, medication, equipment and total performance scores of all 34 PEDs was 42.9%, 50.7%, 43.9% and 46.9% respectively. There was a significant difference in medication availability (p-value = 0.008) and performance scores (p-value = 0.035) across the geopolitical zones of the country. Conclusions: This study reports a global remediable deficiency of emergency care preparedness among PEDs in tertiary care centres in Nigeria. This study highlights the need for training of PED staff in basic and advanced life support and improvement in medication and equipment procurement across Nigeria.
A research report submitted to the Faculty of Health Sciences, University of The Witwatersrand Johannesburg in partial fulfillment of the requirements for the degree of Master of Science (Emergency Medicine) Johannesburg, 2019